PH-sensitive loading/releasing of doxorubicin using single-walled carbon nanotube and multi-walled carbon nanotube: A molecular dynamics study. (April 2020) - Maleki, Reza; Afrouzi, Hamid Hassanzadeh; Hosseini, Mirollah; Toghraie, Davood; Piranfar, Anahita; Rostami, Sara
Highlights: Adsorption and release of anti-cancer drug, DOXORUBICIN, through carbon nanotubes. This study was done by molecular dynamics simulation. DOX adsorption on SWNT and MWNT in neutral pH was stronger than it was in acidic pH. Blood pH is suitable for DOX loading on CNT and CNT-DOX linkage remained stable at this pH. Abstract: Background and objective: Doxorubicin is one of the drugs used to treat cancer, and many studies have been conducted to control its release. In this study, carbon nanotubes have been proposed as a doxorubicin carrier, and the effect of carboxyl functional group on the controlled release of doxorubicin has been studied. Methods: This study has been done by molecular dynamics simulation and was based on changing the pH as a mechanism controller. Results: This work is intended to test the efficacy of this drug carrier for the release of doxorubicin. A comparison was also made between single-walled and double-walled carbon nanotubes to answer the question of which one can be a better carrier for doxorubicin. The study of DOXORUBICIN adsorption and release showed that the DOXORUBICIN adsorption on single-walled carbon nanotube and multi-walled carbon nanotube in neutral pH was stronger than it was in acidic pH, which could be due to the electrostatic interactions between the carboxyl group of nanotubes and DOXORUBICIN. Based on this and according to the investigation of hydrogen bonds, diffusion coefficients, and other results it was clear that the drug release in acidic pH was appropriate for body conditions. Since cancer tissues pH is acidic, this shows the suitability of carbon nanotube in drug delivery and DOXORUBICIN release in cancer tissues. In addition, it was shown that the blood pH (pH = 7) is suitable for DOXORUBICIN loading on the carbon nanotube and carbon nanotube-DOXORUBICIN linkage remained stable at this pH; accordingly, the carbon nanotube could deliver DOXORUBICIN in blood quite well and release it in cancerous tissues. This suggests the carbon nanotubes as a promising drug carrier in the cancer therapy which can be also investigated in experiments. Conclusion: It was revealed that the bonds between multi-walled carbon nanotube and DOXORUBICIN was stronger and this complex had a slower release in the cancer tissues compared to the single-walled carbon nanotube; this can be regarded as an advantage over the single-walled carbon nanotube in the DOXORUBICIN delivery and release.